Association between mycobacterial genotypes and disease progression in Mycobacterium avium pulmonary infection. Issue 10 (23rd June 2009) - Kikuchi, T; Watanabe, A; Gomi, K; Sakakibara, T; Nishimori, K; Daito, H; Fujimura, S; Tazawa, R; Inoue, A; Ebina, M; Tokue, Y; Kaku, M; et al.
Abstract : Background: Non-tuberculous mycobacterial lung disease, most commonly caused by Mycobacterium avium infection, tends to show variable disease progression, and significant disease predictors have not been adequately established. Methods: Variable numbers of tandem repeats (VNTR) were evaluated in 16 mycobacterial interspersed repetitive unit (MIRU) loci from M avium isolates cultured from respiratory specimens obtained from 2005 to 2007. Specifically, the association between VNTR profiles and disease progression was assessed. Results: Among the 37 subjects who provided positive respiratory cultures for M avium during the 2005–6 period, 15 subjects were treated within 10 months following a microbiological diagnosis of progressive M avium lung disease. Nine subjects underwent long-term follow-up (>24 months) without treatment for stable M avium lung disease. Based on a neighbour-joining cluster analysis used to classify M avium -positive subjects according to the VNTR profile, subjects with progressive versus stable lung disease were found to be grouped together in distinct clusters. Further analysis using logistic regression modelling showed that disease progression was significantly associated with the genetic distance of the M avium isolate from an appropriately selected reference (age-adjusted odds ratio 1.95; 95% confidence interval 1.16 to 3.30; p = 0.01 for the most significant model). A best-fit model could be used to predict the progression of M avium lung disease when subjects from the 2005–6 period were combined with those from 2007 (p = 0.003). Conclusion: Progressive lung disease due to M avium infection is associated with specific VNTR genotypes of M avium .